2007
DOI: 10.1159/000102927
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebellum and Language: The Story So Far

Abstract: Background: The cerebellum was traditionally considered to be exclusively involved in the coordination of voluntary movement, gait, posture, balance and motor speech. However, this view was challenged by recent neuroanatomical, neuroimaging and clinical findings, providing preliminary evidence of a cerebellar contribution to linguistic functioning. Aim: To discuss the role of the cerebellum in a variety of linguistic functions and to explore the underlying mechanisms. Methods: A literature search was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 105 publications
5
33
1
Order By: Relevance
“…Clinical, neurophysiological and neuroimaging studies confirm that the cerebellum contributes to grammar processing, in both the expressive and receptive domain [29, 40, 86, 156160]. In the 1990s a possible role of the cerebellum in morphological, syntactic and lexical aspects of grammar was for the first time explored.…”
Section: Cerebellar Contributions To Grammar Processing (M Adamaszek)mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical, neurophysiological and neuroimaging studies confirm that the cerebellum contributes to grammar processing, in both the expressive and receptive domain [29, 40, 86, 156160]. In the 1990s a possible role of the cerebellum in morphological, syntactic and lexical aspects of grammar was for the first time explored.…”
Section: Cerebellar Contributions To Grammar Processing (M Adamaszek)mentioning
confidence: 99%
“…Since then cerebellar involvement in linguistic processes has been studied by advanced neuroimaging methods in healthy subjects and a number of studies have been published focusing on a variety of linguistic dysfunctions following cerebellar lesions of different etiologies in children as well as adults. Reviews of the role of the cerebellum in nonmotor language functions are provided by Gordon [26], Mariën et al [27], Paquier and Mariën [28], De Smet et al [29, 30], Beaton and Mariën [31], Murdoch [32], and Highnam and Bleile [33]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cerebellum has been implicated in speech production and perception (Ackermann et al 2007), and evidence points to this structure's involvement in semantic and grammatical processing (Baillieux et al 2009;De Smet et al 2007). Anomalies of cerebellar cellular organization (Bauman and Kemper 2005) and anatomical structure (Courchesne et al 2005;Schmitz and Rezaie 2008) have long been linked to AD with recent studies also reporting anomalies of activation during the performance of language tasks by individuals with AD (Harris et al 2006).…”
Section: Neurobiological Correlates Of Early Language Delaysmentioning
confidence: 99%
“…De Smet et al [49] reported that cerebellar abnormalities cause word-finding difficulty, disturbed listening comprehension, impaired metalinguistic abilities together with difficulty in understanding social cues.…”
Section: Discussionmentioning
confidence: 99%